2007
DOI: 10.1186/1753-2000-1-10
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study for augmenting atomoxetine with methylphenidate: safety of concomitant therapy in children with attention-deficit/hyperactivity disorder

Abstract: Background: This study examined augmenting atomoxetine with extended-release methylphenidate in children whose attention-deficit/hyperactivity disorder (ADHD) previously failed to respond adequately to stimulant medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
49
0
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 13 publications
0
49
0
2
Order By: Relevance
“…The rate of irritability exceeds that typically observed with either ATMX or OROS MPH alone (Swanson et al 2004;Wilens et al 2006;Newcorn et al 2008). The one prior study of combined ATMX and OROS MPH found no occurrences of irritability; however, only 9 children were exposed to combination treatment (Carlson et al 2007). …”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The rate of irritability exceeds that typically observed with either ATMX or OROS MPH alone (Swanson et al 2004;Wilens et al 2006;Newcorn et al 2008). The one prior study of combined ATMX and OROS MPH found no occurrences of irritability; however, only 9 children were exposed to combination treatment (Carlson et al 2007). …”
Section: Discussionmentioning
confidence: 99%
“…In their one small prior study of combined ATMX and OROS MPH, Carlson et al (2007) reported a 5-bpm increase in HR.…”
Section: Hammerness Et Almentioning
confidence: 99%
See 3 more Smart Citations